What do we know about intravascular fasciitis affecting inferior vena cava? management and report of a case - Mendoza-Moreno, Fernando; Minguez-Garcia, Javier; Diez-Gago, Maria del Rocio; Olmedilla-Arregui, Gabriel; Tallon-Iglesias, Benjamin; Zarzosa-Hernandez, Gustavo; Solana-Maono, Manuel; Arguello-de-Andres, Jesus Manuel (International Surgery Journal, 2017)
Intravascular fasciitis is a rare entity characterized by the proliferation of myofibroblasts and giant cells in relation to small and medium-sized blood vessels. It characterized by a rapid growth and its morphology can simulate other malignant neoplastic processes of more aggressive behavior such as sarcomas. It belongs to a group of benign lesions that affect the subcutaneous tissue and fascia (sometimes to the muscle) sharing characteristics similar to proliferative fasciitis, nodular fasciitis and proliferative myositis. It can sometimes be confused with lesions typical of fibromatosis even. We report a case of a patient with a symptomatic retroperitoneal mass who underwent surgery. The intraoperative findings showed a tumor originating in the inferior vena cava. The histopathological study revealed an intravascular fasciitis.